Effects of Colchicine and 60Co-γ Radiation Treatments on the Leaf Size and Fruit Quality of Kiwifruit ‘Donghong’ - Limei Wang; Qing Liu; Xishi Li; Guanglian Liao; Xiaobiao Xu (Horticulturae)
Colchicine and 60Co-γ radiation are commonly used breeding techniques for kiwifruit, offering advantages such as low cost, rapid execution, and high efficiency. The buds of red-fleshed kiwifruit (Actinidia chinensis) cv. ‘Donghong’ were used as experimental material and subjected to different concentrations of colchicine and different doses of 60Co-γ radiation, respectively. Then, the buds were grafted on rootstock, and the ploidy, leaf size, and fruit quality of mutant fruit were evaluated, and principal component analysis (PCA) and simple sequence repeat markers were used to comprehensively assess and detect genetic variations, respectively. The results indicated that a total of 19 buds successfully germinated, with 13 branches successfully bearing fruit. Significant changes were observed in both leaf and fruit morphology following the mutation treatments. Most of the mutant materials showed significant increases in fruit weight, flesh firmness, and soluble sugar content, while titratable acidity and ascorbic acid content significantly decreased. Notably, the 25Gy 60Co-γ radiation (25d) treatment demonstrated outstanding results, with fruit weight increasing by 256.10%, soluble sugar content rising by 88.29%, titratable acidity decreasing by 29.86%, and ascorbic acid content increasing by 35.60%. PCA results showed that the 25d mutant had the best comprehensive traits. And, except for the 0.4c mutant, all other mutant materials exhibited significant genetic changes at the DNA level.